Implementasi Kurikulum 2013 Dalam Pembelajaran Matematika Dengan Model Problem Based Learning (PBL) Dan Discovery Learning (DL) Pada Siswa Kelas VII Semester Genap SMP Negeri 1 Gondangrejo Tahun Ajaran 2014/2015 - Astuti, Mega, Idris Harta, M.A., Ph.D (2015)
Lots of teachers are still using conventional learning models in delivering the lessons in class, so students are less motivated to learn, especially in the implementation of Curriculum 2013 teachers are required to be more creative in the classroom that can deliver the materials to make children more active, creative and innovative. The purpose of this study was to determine the effect of the model of Problem Based Learning (PBL) and Discovery Learning (DL) in the implementation of the Curriculum in 2013 on learning outcomes. The study was conducted using an experimental method with the number of treatment as much as 2 are grouped into classes for the first experimental model of Problem Based Learning (PBL) and the experimental class to model Discovery Learning (DL). From the results of the analysis using independent t-test without control samples obtained t value of 3.483, while the value of t table (0.05; 62) is 1.625.The results showed that there were significant differences in learning outcomes with the use of the model of Problem Based Learning (PBL) and Discovery Learning (DL) in the implementation of Curriculum 2013. To find a better learning model, can be seen by looking at the average of the learning outcomes of each group. Turns out after further analysis, the groups subjected to the model of Problem Based Learning (PBL) has a higher average of 2,881, this means that the model of Problem Based Learning (PBL) is better than model Discovery Learning(DL).